Peran Psychological Capital dan Dark Triad Memediasi Pengaruh Entrepreneurial Attitude Orientation terhadap Entrepreneurial Intention - Putra, I Putu Suardana; Wibawa, I Made Artha; Riana, I Gede; Dewi, I Gusti Ayu Manuati (Jurnal Bisnis Indonesia, 2024)
Entrepreneurial intention is the desire for entrepreneurship. There are various factors that cancultivate the desire for entrepreneurship. This study aims to analyze and explain the role ofpsychological capital, Machiavellianism, psychopathy, and narcissism in mediating the effect ofentrepreneurial attitude orientation on entrepreneurial intentions. The population in this study isincluded in the limited population because the number of population used has been determined,namely active undergraduate students Class of 2021 at the Badung Regency State University, thesample of this study was 388 people. Data collection methods used were interviews and distributingquestionnaires. The data analysis technique used is SEM-PLS. The results show that entrepreneurialattitude orientation has a positive and significant effect on entrepreneurial intentions,Machiavellianism, narcissism, psychopathy and psychological capital. Machiavellianism has apositive and significant effect on entrepreneurial intentions. Narcissism has no significant effect onentrepreneurial intentions. Psychopathy does not have a significant effect on entrepreneurialintentions. Psychological capital has a positive and significant effect on entrepreneurial intentions.Entrepreneurial attitude orientation has a positive and significant effect on entrepreneurial intentionswith Machiavellianism as a mediating variable. Narcissism, psychopathy and psychological capitalcannot mediate the influence of entrepreneurial attitude orientation on entrepreneurial intentions.Keywords: Psychological Capital; Entrepreneurial Attitude Orientation; Entrepreneurial Intention